IMPLEMENTATION OF EDUCATION AND TEACHER TRAINING MANAGEMENT IN SUPPORTING THE EFFECTIVENESS OF TEACHING AND LEARNING ACTIVITIES AT SMP N 2 PANYABUNGAN - Ahmad Habibi Nst; Aisyah Husaini; Nikmah Nikmah; Kurnia Hayati Hsb; Dara Mutiara Lubis; Winda Amalia; Nurhalima Tussa’diah Lubis; Elsya Juliana Lubis (LPPM Univ. Ibn Khaldun Bogor, 2026)
This study aims to describe and analyze the implementation of educational management and teaching in supporting the effectiveness of teaching and learning activities at SMP N 2 Panyabungan, Mandailing Natal Regency. This study uses a qualitative approach with a case study type. Data collection techniques were carried out through observation, interviews with the principal, teachers, and students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using triangulation techniques to ensure data validity. The results show that the implementation of educational management in schools includes planning learning programs, organizing teacher tasks, implementing academic supervision, and periodic teacher performance evaluations. Teacher management is realized through professional development, competency development, division of tasks according to qualifications, and increasing discipline and responsibility. The effectiveness of teaching and learning activities is seen from increased student engagement, achievement of learning objectives, and a conducive classroom atmosphere. Supporting factors include participatory leadership of the principal and cooperation among school members, while inhibiting factors include variations in teacher competencies. This study concludes that the implementation of structured and sustainable educational management and teaching plays an important role in increasing the effectiveness of the learning process in schools.